Cooperação e competição na indústria de alimentos de amendoim de Marília - SP - Sanches, Marcio Antonio Rodrigues (2003)
This study investigates how some manufacturers of peanut food, working in a food industrial complex in Marília- SP., are availing themselves of cooperation to become more competitiva. Based on a probing research with rural producers, cooperatives, peanut food manufacturers from Marília and institutions supporting food industries, this study describes the main characteristics of the regional peanut agribusiness, as well as its tendencies, and it also identifies the main types of cooperative relationships among the industries analysed, their suppliers, their customers, their competitors and supporting institutions, as class associations, cooperativas etc. lt was verified that, although market transactions prevail in these relationships, some companies are establishing partnerships with suppliers and attracting captive peanut suppliers to meet their requirements of food safety, quality, and others; they are also going into partnerships with distributors to best reach the small retail, and even with competitors, seeking to enlarge the peanut products market. This research points out to the importance of cooperation as a fundamental instrument for competitiveness, not only of peanut food industries, but also of the regional agribusiness of the product, because, although there are good opportunities for increasing the consumption of these products in Brazil and for exporting them, without cooperation the sector would not be able to tackle problems and foresee expansion alternatives.